(untitled) (Journal of Educational Sciences, 2016)
The availability of higher education in recent decades has led to an increase in the number of students in higher education institutions and reduction of higher education quality. Accountability of higher education institutions and quality assurance of higher education have become the subject of heated discussion and debates of a wide range of scholars,politicians and the community in general. One of such popular quality assurance mechanisms in the world is the accreditation of higher education institutions and educational programs, the founder and leader in this field is the USA. For Kazakhstan, the US experience in the field of institutional accreditation, including the development of standards and criteria,is relevant. The Republic of Kazakhstan considers education and ensuring its quality as one of the leading strategic objectives. It is planned that by 2020, 65% of higher education institutions and 30% of technical and vocational institutions will undergo independent institutional accreditation.Accreditation will promote Kazakhstan’s integration into the European area of higher education and the mutual recognition of documents on education. Therefore, this article analyzes the standards and criteria of institutional accreditation of higher education institutions of the USA.